Cropland Loss Under Different Urban Expansion Patterns in China (1990–2020): Spatiotemporal Characteristics, Driving Factors, and Policy Implications - Chengrui Mao; Shanshan Feng; Canfang Zhou (Land)
It is well established that China’s rapid urban expansion has led to a substantial loss of cropland. However, few studies have examined how different urban expansion patterns contribute to cropland consumption, which has hindered the formulation of sustainable urban development and cropland protection policies. To fill this gap, we analyzed the occupation of cropland under three urban expansion patterns (leap-frogging, edge-spreading, and interior filling) in China from 1990 to 2020, using long-term land use data. The dominant driving forces of cropland loss were then explored using the XGBoost model and SHAP values. Our findings indicate that urban expansion in China from 1990 to 2020 resulted in a 6.3% reduction in cropland, with edge-spreading (4.0%) contributing the most, followed by leap-frogging (2.1%) and interior filling (0.2%). Change in urban intensity (CUI) proved to be the most critical driver of cropland loss, with SHAP values of 0.38, 0.28, and 0.37 for edge-spreading, leap-frogging, and interior filling, respectively. Over time, the driving forces evolved from a single demographic-economic dominance to a more diversified and integrated set of drivers. Based on these findings, we propose tailored planning and policies for different urban expansion patterns; for regions dominated by edge-spreading, stricter controls on urban boundaries and stronger land use planning constraints are required. For regions with prominent interior filling expansion, efforts should be made to improve internal land use efficiency while preserving existing cropland spaces. In regions characterized by leap-frogging expansion, further optimization of construction land allocation is needed to reduce the occupation of productive suburban cropland. These findings not only offer new empirical evidence for understanding the interplay between urban expansion and cropland conservation but also provide transferable insights that can inform sustainable land-use planning and cropland protection strategies in other rapidly urbanizing regions facing similar challenges.